2021
DOI: 10.1007/s11282-021-00518-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical guidelines for the application of panoramic radiographs in screening for osteoporosis

Abstract: Osteoporotic fractures are associated with an increased risk of subsequent fractures, a higher rate of mortality, and incremental medical costs. Incidental findings, which include some measurements related to the mandibular inferior cortex and the alveolar trabecular bone pattern of the mandible determined on panoramic radiographs, are considered to be a useful tool for identifying asymptomatic individuals at risk of having osteoporosis and/or fragility fractures. We undertook a worldwide literature survey and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 91 publications
0
20
1
3
Order By: Relevance
“…The choice between high sensitivity or high specificity will probably depend on the health system in the specific country. Taguchi et al [4] concluded that postmenopausal women with a severely eroded mandibular inferior cortex may have an increased risk of having osteoporosis/fragility fractures. Both Taguchi et al [4] and Devlin et al [38] recommend that only those patients with the thinnest mandibular cortices; i.e., 3 mm or less, should be referred for further osteoporosis investigation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The choice between high sensitivity or high specificity will probably depend on the health system in the specific country. Taguchi et al [4] concluded that postmenopausal women with a severely eroded mandibular inferior cortex may have an increased risk of having osteoporosis/fragility fractures. Both Taguchi et al [4] and Devlin et al [38] recommend that only those patients with the thinnest mandibular cortices; i.e., 3 mm or less, should be referred for further osteoporosis investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Taguchi et al [4] concluded that postmenopausal women with a severely eroded mandibular inferior cortex may have an increased risk of having osteoporosis/fragility fractures. Both Taguchi et al [4] and Devlin et al [38] recommend that only those patients with the thinnest mandibular cortices; i.e., 3 mm or less, should be referred for further osteoporosis investigation. In countries like the UK and Sweden, where health care is free or extremely cheap, the workload for primary care is heavy, and a high specificity is thus warranted for dentists involved in identifying individuals at risk, thereby avoiding unnecessary referrals to physicians.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bone loss in the jaw is involved in osteoporosis and may act as a screening predictor for osteoporosis and fracture risk. The mandibular cortical index, mandibular inferior cortical width below the mental foramen, and alveolar trabecular bone pattern of the mandible are useful for screening of low skeletal bone mineral density (BMD) and osteoporosis ( 323 ). The relative risk of future fracture of the sparse trabecular pattern of the mandible is higher than that of cortical erosion in perimenopausal and older women ( 324 ).…”
Section: Inflammasomes In Inflammatory Osteolysis Of the Alveolar Bone And Jawsmentioning
confidence: 99%